Development of a rocket recovery system - Nur Fitrina, Mat Nawi (2013)
The design, fabricate and testing of a rocket recovery system is presented in this report. Recovery system is important for a rocket for low cost of fabricating the rocket and the flight data analysis. The recovery system chosen for the rocket is a parachute recovery system. The recovery system is divided into two parts; the parachute and the ejection system. In this report, six different designs are fabricated. Drop test of the parachutes was conducted to find the design for the parachute. The test shows that the semi- ellipsoidal parachute is the best parachute that can support an empty rocket mass of 2.5kg with the descent range is 5.98m/s. The parachute recovery system constructed in this project will be integrated with the rocket body and powered by a solid propellent rocket motor.